Implementation of Group Counseling Using the Johari Window Technique to Enhance Student Self-Disclosure - Alamsyah, Muh. Nur; Indreswari, Henny; Khairul Bariyyah (ILIN Institute, 2024)
This research aims to evaluate the effectiveness of the Johari Window technique in group counseling and to investigate how this technique can enhance students' self-disclosure. It is anticipated that with an improved understanding of self-disclosure through the Johari Window technique, students will be able to reap maximum benefits from the educational process, not only in academic aspects but also in their social and emotional development. The method employed in this research is a Systematic Literature Review (SLR), which involves systematic steps to search, select, and analyze relevant literature sources. During the data collection process, this study examined and compiled a variety of publication types, including articles, journals, dissertations, theses, and dissertations from various sources related to the research topic. The findings indicate that the Johari Window technique is effective in group counseling for enhancing student self-disclosure.